Visual evoked potentials in dissociated vertical deviation: a reappraisal. Issue 4 (April 1989) - Kriss, A; Timms, C; Elston, J; Taylor, D; Gresty, M
Abstract : Pattern reversal and flash evoked potentials were recorded in 13 children with dissociated vertical deviation (DVD). No electrophysiological evidence was found to support the notion that patients with DVD have an anomalous (albinoid) projection of visual fibres originating from the temporal retina of each eye. However, DVD patients had significantly smaller monocular and binocular pattern evoked responses than age matched controls. Explanations are given for this finding and for the occipital VEP asymmetries reported by other workers.